Use of DNA pooling in large-scale association studies - Sham, Pak (Henry Stewart Talks, 2004)
Principles of DNA pooling, The cost benefit, Getting the quantification right, SNaPshot, Estimating and incorporating measurement error, Consequences of differential amplification, Pool construction vs. genotyping errors, Determining optimal design, Family designs, Stratified designs, Design for quantitative traits, Methods for statistical analysis, Case study: ADHD, Approaches to haplotype analysis in DNA pooling, Recommendations
Archived at 2021/02/25